Factors of Land Use Change in Bandung Regency, West Java for 2 Decades - Abriyantoro, Danang; Hasrianti, Hasrianti (CV. Publikasi Indonesia, 2024)
The research investigates the land use patterns that have developed in Bandung Regency, located in West Java, over the past twenty years. The region has undergone a significant transformation due to rapid urbanization caused by population growth and economic development. This transformation has led to the conversion of agricultural land and forests into residential, commercial, and industrial areas. This transition provides economic benefits, but it also brings difficulties such as reduced arable land, environmental damage, and concerns about food security. The research focuses on the socio-economic factors driving these changes, the environmental impacts they cause, and the actions taken by local and regional governments through policy and planning initiatives. Descriptive qualitative research methods are very suitable for investigating complex phenomena such as patterns of land use change. The results emphasize the need to implement a comprehensive and sustainable land use strategy that effectively manages the competition for development and environmental conservation interests. This will ensure the region's long-term ability to survive and adapt to challenges while maintaining its sustainability.